2022
DOI: 10.4081/monaldi.2022.2117
|View full text |Cite
|
Sign up to set email alerts
|

Identifying psychological antecedents and predictors of vaccine hesitancy through machine learning: A cross sectional study among chronic disease patients of deprived urban neighbourhood, India

Abstract: COVID-19 vaccine hesitancy among chronic disease patients can severely impact individual health with the potential to impede mass vaccination essential for containing the pandemic. The present study was done to assess the COVID-19 vaccine antecedents and its predictors among chronic disease patients. This cross-sectional study was conducted among chronic disease patients availing care from a primary health facility in urban Jodhpur, Rajasthan. Factor and reliability analysis was done for the vaccine hesitancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This may be because the first phase of vaccination targeted frontline workers, social workers, individuals with comorbidities, and the elderly above 60 years. In the elderly population, mean daily doses of vaccine were higher in CVE than in RCV; few studies have shown vaccine hesitancy is higher in the elderly [3] . The strategies used in CVE, like mobile vaccination vans, helped increase uptake in the elderly.…”
Section: Discussionmentioning
confidence: 96%
“…This may be because the first phase of vaccination targeted frontline workers, social workers, individuals with comorbidities, and the elderly above 60 years. In the elderly population, mean daily doses of vaccine were higher in CVE than in RCV; few studies have shown vaccine hesitancy is higher in the elderly [3] . The strategies used in CVE, like mobile vaccination vans, helped increase uptake in the elderly.…”
Section: Discussionmentioning
confidence: 96%
“…we read the publication by Rustagi et al on "Identifying psychological antecedents and predictors of vaccine hesitancy through machine learning: A cross sectional study among chronic disease patients of deprived urban neighbourhood, India"[1] with a great interest. Rustagi et al concluded that "Higher scores for COVID-19 health literacy and preventive behaviour, along with family support, monthly income, past COVID-19 screening, adherence to medications and age were associated with lower vaccine hesitancy"[1].…”
mentioning
confidence: 99%